BCT672: Professional ethics and integrity in construction / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2018)
The general aim of the course is to provide a basic knowledge and understanding on the background of local construction industry scenario, organizations and practiced. The course also covers an introduction to building elements and plant machinery used, theoretical study with emphasis on the methods of executing preliminary works, temporary works, sub-structure and load bearing wall construction.